Synthesis, characterization and actuation behavior of polyaniline-coated electroactive paper actuators - Kim, Jaehwan; Yun, Sung-Ryul; Deshpande, S. D. (Polymer International, 2007)
This investigation deals with the synthesis, characterization and actuation behavior of conductive polyaniline-coated electroactive paper actuators. The actuator is made by electrochemical deposition of conductive polyaniline on a cellulose paper. The aim of the investigation was to improve the bending displacement of electroactive paper actuators. The displacement outputs of the actuators show that a trilayer is better than a bilayer configuration. The nature of the dopant ion used in the electro-generation affects the performance. A change in humidity plays a vital role in actuation performance of the actuators. Comparing the performance of electroactive paper actuators with and without a conductive polyaniline coating, the coating improves the displacement output threefold. Finally, the actuation principle mechanism is addressed. (C) 2007 Society of Chemical Industry.
Keywords: bending actuator; conducting polymer; electroactive polymer (EAP); polyaniline